Dietary and lifestyle disease indices and caecal microbiota in high fat diet, dietary fibre free diet, or DSS induced IBD models in ICR mice. (August 2017) - Kuda, Takashi; Yokota, Yasushi; Shikano, Ayane; Takei, Moemi; Takahashi, Hajime; Kimura, Bon
Highlights: ICR mice were given CE-2, DSS, Quick Fat, or AIN-76 without cellulose (-). Damage of colon epithelial tissue were found in the Quick Fat and AIN-76 (-) groups. Gram staining of caecal contents showed that sporulation was markedly promoted by DSS. 16S rDNA amplicon sequencing of caecal contents showed the typical microbiota in each group. Firmicutes / Bacterioidetes ratio was considerably high in the AIN-76 (-) group. Abstract: To examine the relationship between multiple lifestyle related diseases and inflammatory bowel disease (IBD), ICR mice were fed normal chow (CE-2), CE-2 with dextran sodium sulphate (DSS) in drinking water, a high fat diet (Quick Fat), or a fibre-free diet (AIN-76(-)). The plasma LDL/HDL cholesterol ratio was generally higher in the AIN-76 (-) and DSS groups. Shortening of the colon, an indicator of IBD, was prominent in the AIN-76(-) group. Damage of colon epithelial cells and layers was considerable in the DSS group, and was also observed in the Quick Fat and AIN-76(-) groups. Gram staining of caecal contents revealed that sporulation was promoted by DSS. The 16S rDNA amplicon sequencing of caecal contents showed that the Firmicutes/Bacterioidetes ratio (F/B) was considerably high in the AIN-76(-) group. In addition to Turicibacter and Bacteroides, Akkermansia muciniphila, which reportedly ameliorates obesity and increases the immune reaction, was high in the DSS group.